PENGARUH DESAIN PENCAHAYAAN ALAMI TERHADAP KENYAMANAN VISUAL DAN PSIKO-VISUAL PADA TANATAP RING GARDEN COFFEE SHOP AMPERA JAKARTA - Firmansyah Putri, Ghea Helena; Dewi Pangestu, Mira (Jurnal Riset Arsitektur, 2023)
Abstract - At the moment, daylight is a significant element in designing a building. Daylight design needs toconsider visual comfort and psycho-visual comfort in a building. Visual comfort calculate the quality andquantity of daylight in an area. Meanwhile, psycho-visual comfort relates to the experience or atmosphere ofdaylight in a room that af ects the visual perception, emotion, and behaviour of space users.Tanatap Ring Garden Cof ee Shop Ampera Jakarta is a cafe designed by RAD+ar, which have functions fordining, hanging out, and meeting. Public Park is the main concept of the Tanatap Ring Garden with sustainablearchitecture and a tropical building approach that responds to the climate on site. The application of thisconcept uses daylight as the main lighting from morning to evening. In addition to saving energy, the use ofdaylight is also designed to create an intimate atmosphere at the entrance and bar area, then an openatmosphere whose intimacy is reduced by the presence of an outdoor as a focal point of this building. Withvarious activities and designs of daylight openings, this aspect af ects the visual and psycho-visual comfort ofvisitors at Tanatap. Therefore, the purpose of this study was to determine the ef ect of light opening design onthe quantity and quality of daylight. This study is also to determine the extent to which the design of daylightopenings af ects the visual comfort and psycho-visual comfort of visitors at the Tanatap Ring Garden AmperaCafe Jakarta.This research uses descriptive - evaluative methods with quantitative approaches. A quantitative approach isused to obtain data on the quantity and quality of daylight to determine visual comfort at Tanatap with digitalsimulation techniques using LightStanza. A quantitative approach was used to obtain data on theperception-emotion-behaviour of respondents with a questionnaire regarding the psycho-visual comfort ofvisitors to Tanatap Ampera. Then, data on the existing condition of visual and psycho-visual comfort werecompared to confirm the achievement of the concept of daylight designed by Tanatap architects.This study resulted in several conclusions. First, the visual comfort in the existing condition in terms of thequantity and quality of daylight at the Tanatap cafe already meets existing standards and is in accordance withthe concept of the Tanatap architect. Second, psycho-visual comfort has an important role in realizing the visualperception of visitors so as to create a comfortable, open, and intimate atmosphere, as well as an impression ofbeing in a garden in accordance with the concept of daylight from the architect Tanatap. Third, the design ofdaylight openings has provided visual and psycho-visual comfort with categories appropriate to be very suitablefor visitors in the research area.Keywords: café, daylighting, natural lighting, visual comfort, psycho-visual comfort, Tanatap Cof ee Shop